The intergenerational effect of mother's depression on their young adult children's depression - Jaewon Lee; Jennifer Allen (Archives of Depression and Anxiety - Peertechz Publications, 2021)
Women are often more likely to report mental health problems such as depression compared to men [1,2]. As individuals age, people with children are more likely to be depressed [3]. Therefore, mothers are at particularly high risk for depression, and their depression negatively influences their children's development [4,5]. Even though it is important to take into account the effect of mother's depression on their children's psychological health, empirical evidence about the intergenerational effects of depression at three points in time does not exist.